A dreadful splendor eaudiobook A novel. - Myers, B.R (HarperAudio, 2022)
INTERNATIONAL BESTSELLER WINNER OF THE MARY HIGGINS CLARK AWARD "This gem of a book sparkles with wit and originality. . . . There is no shortage of tricks and feints in this excellent novel and Genevieve is a delightful character." — The Globe and Mail "A spooky gothic romance with impeccable vibes. I loved this!"" — Erin Sterling, New York Times bestselling author of The Ex Hex and The Kiss Curse In this wickedly whimsical Gothic murder mystery brimming with romance, betrayals, and chills, a fake spiritualist is summoned to hold a séance for a bride who died on the eve before her wedding, but as nefarious secrets are revealed, the line between hoax and haunting blurs. Be careful what you conjure... In Victorian London, Genevieve Timmons poses as a spiritualist to swindle wealthy mourners—until one misstep lands her in a jail cell awaiting the noose. Then a stranger arrives to make her a peculiar offer. The lord he serves, Mr. Pemberton, has been inconsolable since the tragic death of his beautiful bride-to-be. If Genevieve can perform a séance persuasive enough to bring the young lord peace, she will win her freedom. Soothing a grieving nobleman should be easy for someone of Genevieve's skill, but when she arrives at the grand Somerset Park estate, Mr. Pemberton is not the heartbroken lover she expected. The surly—yet exceedingly handsome—gentleman is certain that his fiancée was murdered, even though there is no evidence. Only a confession can bring justice now, and Mr. Pemberton decides Genevieve will help him get it. With his knowledge of the household and her talent for illusion, they can stage a haunting so convincing it will coax the killer into the light. However, when frightful incidents befall the manor, Genevieve realizes her tricks aren't required after all. She may be a fake, but Somerset's ghost could be all too real... A Dreadful Splendor is delicious brew of mystery, spooky thrills, and intoxicating romance that makes for a ghoulishly fun and page-turning read. ""A delightful mix of gothic, mystery, and romance. I had such fun reading this book!"" — Gwenda Bond, New York Times bestselling author of Not Your Average Hot Guy